Solve x^2 - 9 = 4x + 12

x2 - 9 = 4x + 12 x2 - 9 - 4x = 12 x2 - 9 - 4x -12 = 0 x2 - 4x -21 = 0 Factorise into form (x + ?)(x + ?) Factors of -21 are +7 and -3 or -7 and +3 (x + 7)(x - 3) = x2 + 7x - 3x -21 = x2 + 4x -21 which isn't what we want so it must be (x - 7)(x + 3)(x - 7)(x + 3) = 0 so x = 7 and x = -3

Answered by Kira P. Maths tutor

3315 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

What is a vector?


An item costs £65 but requires an additional 20% VAT to be added. How much change will you get from £100


The area of a square is 49cm^2. The perimeter of this square is equal to the circumference of a circle. Calculate the radius of the circle to 1 decimal place.


Draw the following inequality on a graph: x^2+4x+1<-2


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences